A New Grounding Resistance Reduction Method for Wind Turbines by Grounding Grid Connection in Limited Areas - Hu, Yuanchao; Liu, Zhixiang; Huang, Tao; An, Yunzhu; Shen, Wentao; Hu, Shangmao; Ma, Chenghui; An, Bingchen; Chen, Dan (Frontiers in Energy Research, 2022)
Restricted by cultivated land vegetation, road construction, and land acquisition compensation costs, the grounding electrode extension method is not applicable for grounding resistance reduction of some wind turbines in limited areas. A new grounding resistance reduction method is proposed and verified for wind turbines by connecting nearby wind turbine grounding grids. To study the efficiency of the proposed method, the grounding characteristics of connected grounding grids are calculated. Simulation results indicate that the grounding resistance of connected grounding grids is smaller than that of box extension grounding grids. The grounding characteristics of the grounding grid connection are affected by grounding current frequency and material parameters. The grounding grid connection increases the current dispersion area and reduces the ground potential rise of the grounding conductor.